2011
DOI: 10.1143/jjap.50.124101
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of Electron and Ion Transfer in All-Solid Ion-Transfer Device Made of Transition Metal Cyanide Films

Abstract: The state-selective dissociation dynamics for anionic and excited neutral fragments of gaseous SiCl 4 following Cl 2p and Si 2p core-level excitations were characterized by combining measurements of the photoninduced anionic dissociation, x-ray absorption and UV/visible dispersed fluorescence. The transitions of core electrons to high Rydberg states/doubly excited states in the vicinity of both Si 2p and Cl 2p ionization thresholds of gaseous SiCl 4 lead to a remarkably enhanced production of anionic, Si − and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Nano spaces within the framework enable the reversible storage of guest species (Na + and H 2 O) [15,16]. This property of M-PBAs results in various functionalities, such as lithium/sodium/potassium ion secondary batteries , tertiary batteries [5][6][7][8][9][10], electrochromism [46][47][48][49][50][51][52][53], and so on. Shibata et al [48] reported that an all-solid-state ion transfer device, in which only Na + ions but not electrons can pass through the interface, for electrochromic devices can be fabricated with the physical junction of two PBA thin films.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nano spaces within the framework enable the reversible storage of guest species (Na + and H 2 O) [15,16]. This property of M-PBAs results in various functionalities, such as lithium/sodium/potassium ion secondary batteries , tertiary batteries [5][6][7][8][9][10], electrochromism [46][47][48][49][50][51][52][53], and so on. Shibata et al [48] reported that an all-solid-state ion transfer device, in which only Na + ions but not electrons can pass through the interface, for electrochromic devices can be fabricated with the physical junction of two PBA thin films.…”
Section: Introductionmentioning
confidence: 99%
“…This property of M-PBAs results in various functionalities, such as lithium/sodium/potassium ion secondary batteries , tertiary batteries [5][6][7][8][9][10], electrochromism [46][47][48][49][50][51][52][53], and so on. Shibata et al [48] reported that an all-solid-state ion transfer device, in which only Na + ions but not electrons can pass through the interface, for electrochromic devices can be fabricated with the physical junction of two PBA thin films. The electron barrier at the physically formed interface was attributed to the naturally formed water sheet [48], which acts as a pseudo electrolyte layer.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To make a stepwise distribution of x, we performed initial oxidization process of the NCF90 film. Shibata et al 37) reported that the contact area of two PBA thin films in the air is permeable to Na + but not to electrons. Therefore, we contacted the left half of the NCF90 thin film with a preoxidized NCF90 film (x = 0.0) film with a thickness of 0.92 μm.…”
mentioning
confidence: 99%